Meso-Cenozoic Tectonic Evolution of the Kexueshan Basin, Northwestern Ordos, China: Evidence from Palaeo-Tectonic Stress Fields Analyses - Cheng, Yongzhi; Gao, Rui; Lu, Zhanwu; Li, Wenhui; Su, He; Han, Rubing; Chen, Hao (Frontiers in Earth Science, 2022)
The Kexueshan Basin in the western Ordos Block is characteristic of typical regional superimposed folds in the Jurassic strata, documenting the main tectonic shortening since the Mesozoic. Field structural investigation, fault kinematic analysis, together with regional structural analysis, we reconstruct two-phase tectonic stress fields related to crustal shortening. Synthesizing the regional structural analysis and geochronology, two stages of tectonic evolution are proposed in the Kexueshan Basin since the late Mesozoic. In the mid-late Middle Jurassic (J2), controlled by NW-SE compaction, NW-SE structures formed in the Kexueshan Basin on the western margin of the Ordos Block, marked by NE- to NNE-trending folds and thrust faults. Growth strata found in the study area constrain the starting time of the NW-SE structures. This shortening is likely related to a combination of the southward convergence of the Siberian plate and the northwestward subduction of the Pacific plate. In the end Cenozoic (N12-N2), the tectonic stress field was transformed to NE-SW compression, resulting in the development of NW- to NNW-trending fold structures, which were superimposed on early NE- to NNE-trending structures to produce regional superimposed folds. The tectonic shortening coincided with the northeastward growth of the Tibetan Plateau.